The skills balance in Germany's import intensity of exports: An input-output analysis - Udo Ludwig; Hans-Ulrich Brautzsch (Intereconomics, 2014)
In the decade prior to the economic and financial crisis, Germany's net exports increased in absolute terms as well as relative to the growing level of import intensity of domestically produced export goods and services. This article analyses the direct and indirect employment effects induced both by exports as well as by of the import intensity of the production process of export goods and services on the skills used. It shows that Germany's export surpluses led to positive net employment effects. Although the volume of imports of intermediate goods increased and was augmented by the rise in exports, it could not undermine the overall positive employment effect.
Keywords: 330; Außenhandel; Beschäftigungseffekt; Humankapital; Außenhandelsstruktur; Input-Output-Analyse; Deutschland